Households' Inflation Perceptions and Expectations: Survey Evidence from New Zealand - Bernd Hayo; Florian Neumeier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
In this paper, we study how inflation is viewed by the general population of New Zealand. Based on unique representative survey data collected in 2016 and using descriptive statistics and multivariate regressions, we explore various aspects of how laypersons perceive inflation and form inflation expectations. We focus on how an individual's economic situation, information search and interest in inflation, economic knowledge, and attitudes and values are related to inflation perception and expectation, as well as the individual's reaction to them. We interpret our findings as a clear indication that laypersons' knowledge about inflation is much better described by the imperfect information view prevailing in social psychology than by the rational actor view typically assumed in economics.
Keywords: E52; E58; Z10; 330; Inflation perception; inflation expectation; New Zealand; monetary policy; household survey.